An Eye for an Eye: Examining Public Support for Vigilante Behaviour - Stone, Louise Mary (Auckland University of Technology, 2016)
The purpose of this thesis was to examine the relationship between actor ethnicity and public support for vigilante behaviour. The study considered how actor ethnicity could influence participants’ empathy for and blame towards a vigilante’s victim, as well as the outrage towards and desire to punish a vigilante. The predominate theory guiding the project was Haas’ (2010) situational hypothesis, in addition to concepts such as in-group favouritism, stereotypes, sympathy perspective, and racial threat theory. This project considered whether such theories – which have been used to explain perceptions of crime – were applicable to the distinctive situation of vigilantism. To examine this topic, two vignettes were constructed – one describing a precipitating crime and one outlining the vigilante response. Excluding the manipulation of vigilante and victim ethnicity, the content of these vignettes remained identical. To gauge participants’ response, a questionnaire was developed to measure: support for vigilantism in general, responses to the precipitating crime and vigilante response, right-wing authoritarianism, and participant demographics. Participants were recruited using convenience sampling via university lectures and tutorials, as well as social media accounts. The anonymous, online survey was completed by a total of 126 participants. Various quantitative techniques were used to analyse the data collected; including, Pearson’s correlation, independent samples t-test, one way ANOVA, two way ANOVA. The results indicated moderate support for vigilantism as a general concept. In terms of the specific vignettes, it was found that the victim and offender of the precipitating crime were perceived differently to those within the vigilante scenario. In particular, participants prescribed less empathy and more blame towards the vigilante’s victim then they did the precipitating victim. Furthermore, in comparison to the precipitating offender, respondents exhibited less outrage towards the vigilante and a lesser desire to punish them. With regards to actor ethnicity, the study found that the ethnicity of the vigilante’s victim did not influence participant responses, nor did it significantly interact with vigilante ethnicity. The research identified one statistically significant finding related to the vigilante’s ethnicity – participants expressed a significantly greater desire to punish the vigilante when they were portrayed as being ‘light skinned’ as opposed to ‘dark skinned’. This thesis focused on a topic that had not been considered by prior research and consequently began the process of addressing a gap present within the literature. The findings seem to suggest that the current theories surrounding ethnicity and perceptions of crime may not be applicable to the unique circumstances of vigilantism. Further research is required before a well-supported conclusion can be reached.
Keywords: Vigilantism; Ethnicity; Perceptions; Discrimination